Effectiveness of Technology Use in Indonesian High Schools: Student Engagement, School Capacity, Teacher Performance - Widodo, Yohanes Bowo; Akbar, Khoironi Fanana (International Journal of Business, Law, and Education, 2024)
The present research investigates the intricate interplay among student engagement, school capacity, teacher performance, and the proficient implementation of technology within secondary institutions in Indonesia. This study employs a quantitative methodology to incorporate these constructs into a comprehensive model by utilizing Structural Equation Modeling with Partial Least Squares. The study surveyed 243 educators using a stratified random sample, which yielded valuable information regarding demographic characteristics, patterns of technology usage, and the intricate interrelationships among the variables identified. The robust validity and reliability of the measurement model validated the efficacy of the chosen indicators. Significant positive correlations were identified through path analysis among student engagement, school capacity, teacher performance, and technology effectiveness. By drawing inspiration from the Integrated Educational Technology Ecosystem theory, this model enhances the theoretical comprehension of technology integration specifically within the domain of secondary schools in Indonesia. In addition, recommendations and practical implications for policymakers, educators, and future research are addressed.